CARBON DIOXIDE AND METHANE EMISSIONS FROM CALCAREOUS-MARLY ROCK UNDER STRESS: EXPERIMENTAL TESTS RESULTS - Martinelli G.; Plescia P. (My University, 2005)
The identified emissions of abiogenic carbon dioxide, carbon monoxide and methane are generally attributed to volcanic activity or to geochemical processes associated with thermometamorphic effects. In this paper we show another possible abiogenic source of emission, induced by mechanical, and not thermal, stresses. We investigated the mechanochemical production of carbon dioxide and methane when friction is applied to marly-type rock and studied the mechanisms determining the strong CO2 and CH4 emissions observed. A ring mill was used to apply friction and oriented pressure upon a synthetic calcite-clay mixture of varying proportions. We found that the CO2 and CH4 release versus the grinding action has a non-linear trend reflecting the behaviour of decreasing crystallinity, which indicates a close link between crystallinity and gas production. For the CO2 emission, we propose a release mechanism connected with the friction-induced fractures and the increase in structural disorders induced by creep in the lattice. The CH4 emission could be explained by a Sabatier reaction in which CO2 and hydrogen are involved to form CH4 and water.
Keywords: EARTHQUAKE PRECURSORS; GAS GEOCHEMISTRY; GREENHOUSE GASES